Analysis of the Influence of Gear Clamping Tilt Error on Cylindrical Gear Accuracy in Testing - Zhang Guozheng; Han Jiang (Jixie chuandong)
Aiming at the problem that the tilting error caused by the clamping gear with expandable core shaft affects the accuracy test of the gear,the cause of the tilting error is analyzed based on positioning principle of gear clamping. By using the Small Displacement Torsor（ SDT） Method,the tooth surface model with error is constructed,the influence of clamping tilting error on gear deviation accuracy is analyzed. The nine deviation indexes of three clamping angles of gears are detected by gear detection center,playing table alignment method setting three clamping angle,the influence law of clamping tilting error on gear precision detection is obtained.The results show that,the great influence of clamping tilting error on gear detection accuracy is fHβ,Fβ and Fp,the less important influence is ffα,fHα and Fα,the influence is insensitive or subtle is ffβ,fpt and Fr,so that further improve the gear clamping process theory.